CEO Characteristics and Green Innovation: A Systematic Literature Review - Nurul Fitriani; Selma Putri Safira; Putri Dwi Aprilia Nur Khasanah; Yulianti Raharjo (Journal of Applied Accounting and Taxation, 2024)
This study employs a systematic literature analysis to identify research gaps and opportunities on the influence of CEO qualities on green innovation. By critically evaluating the shortcomings of current research and synthesizing pieces from reliable, Scopus-indexed journals, it adds to the body of knowledge on green innovation. The study's conclusions point out gaps in the literature, pointing out that prior studies have mainly concentrated on green innovation in industrialized countries"”particularly China. Additional investigation is required to examine particular characteristics of CEOs, such as dualism, turnover, and other psychological attributes. Policymakers, practitioners, and academics can all profit from these insights.